Investigating genetic links of vitamin D metabolism pathway genes (CYP2R1, CYP27B1, CYP24A1, and DBP) in Multiple Sclerosis patients - Laith AL-Eitan; Asaad Ataa (PLoS ONE, 2025)
Multiple sclerosis (MS) is believed to result from a complex interplay of behavioral, genetic, and environmental risk factors. Furthermore, some studies indicated that vitamin D deficiency is linked to the emergence of different diseases, including MS. This study aims to determine the genetic associations between vitamin D metabolism gene polymorphisms and MS susceptibility in the Jordanian community. A total of 388 samples (192 MS patients and 196 controls). Genotypes for CYP2R1 (rs10741657, rs12794714), CYP27B1 (rs10877012), CYP24A1 (rs2248359), and DBP (rs7041, rs4588) were determined by PCR/RFLP assay method. The study revealed a significant association with increased MS risk in SNPs rs10877012 (C/A, P = 0.0002) of the CYP27B1 gene and rs4588 (A/A, P = 0.04) of the DBP gene. Additionally, the haplotypes of the CYP2R1 gene revealed a significant association with MS patients and controls (GG, p = 1e-04; AA, p < 0.0001). Moreover, only a SNP rs4588 of the DBP gene has been significantly associated (P = 0.04) with a clinical phenotype of multiple sclerosis and vitamin D deficiency. Understanding these genetic variations in multiple sclerosis susceptibility genes can help healthcare professionals improve early diagnosis and develop personalized treatment options.